Tracking key CAADP indicators and implementation processes [In the 2019 ATOR] - Makombe, Tsitsi; Tefera, Wondwosen; Ulimwengu, John M. (International Food Policy Research Institute, 2019)
The Comprehensive Africa Agriculture Development Programme (CAADP) is a continentwide framework for accelerating broad-based economic growth and progress toward poverty reduction and food and nutrition security through an agriculture-led growth strategy. It was officially adopted by the African Union (AU) heads of state and government in the 2003 Maputo Declaration on Agriculture and Food Security with two main targets: achieving a 6 percent annual agricultural growth rate at the national level and allocating 10 percent of national budgets to the agriculture sector. In 2014, the AU heads of state and government reaffirmed their commitment to CAADP by adopting the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. In the Malabo Declaration they made seven broad commitments, including upholding the CAADP principles and values; enhancing investment in agriculture; ending hunger and halving poverty by 2025; boosting intra-African agricultural trade; enhancing resilience to climate variability; and strengthening mutual accountability for actions and results by conducting a Biennial Review (BR) of progress made in achieving the commitments.